Case Study of the Development of the 1998 Tribal State Agreement in Minnesota - Campbell, Evelyn (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2010)
This paper focuses on a recent qualitative study of the 1998 Indian Child Welfare Tribal State Agreement in Minnesota. The purpose of this study was to document the history of how American Indian women initiated legislative changes at the state level to strengthen the Indian Child Welfare law. This paper will identify the process used by these women and an American Indian workgroup and document the workgroup’s recommendations for other states and tribes interested in creating similar agreements.